Preparation method of chemical bath deposition tin oxide film based on inert atmosphere protection
By using inert atmosphere to protect and regulate the Sn2+/Sn4+ ratio in the chemical bath deposition process, the problem of difficult to regulate the energy band structure and thickness of the tin oxide film is solved, and the preparation of high-efficiency perovskite solar cells is achieved.
Patent Information
- Application Number
- CN202411422051.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-02-18
AI Technical Summary
When preparing tin oxide thin films with existing chemical bath deposition processes, it is difficult to accurately regulate their band structure and thickness, affecting the performance of perovskite solar cells.
Using inert atmosphere protection, SnCl4 is introduced into the SnCl2 solution, and the ratio of Sn2+ and Sn4+ is precisely regulated, and the hydrolysis process of chemical bath deposition is regulated, thereby controlling the thickness and energy band structure of the tin oxide film.
The precise control of the energy band structure of the tin oxide film was achieved, and a moderate thickness of SnOx film was prepared, which improved the photoelectric conversion efficiency of perovskite solar cells to reach more than 26%.
Smart Images

Figure CN119465107A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemistry and photovoltaics, and in particular relates to a preparation method of a tin oxide film deposited by a chemical bath under inert atmosphere protection. Background Art
[0002] As a representative of clean energy, solar energy is becoming increasingly important in the energy field. Perovskite solar cells (PSCs), as a representative of the new generation of solar cells, have unique advantages over other similar products, such as easy manufacturing, low production cost, and compatibility with flexible electronic products, making them potentially competitive with silicon-based solar cells, which currently dominate photovoltaic cells.
[0003] At present, high-efficiency perovskite solar cells are mostly made of tin oxide (SnO) prepared by chemical bath deposition (CBD). x ) as the electron transport layer. The small-area PSCs prepared based on this process have a high photoelectric conversion efficiency (PCE) and have very broad prospects for industrial application. x The band structure can promote carrier transport, inhibit charge accumulation and non-radiative recombination at the interface, thereby improving device performance. Conventional CBD solution is prepared from hydrochloric acid, urea, thioglycolic acid, stannous chloride dihydrate and water. 2+ Oxidation of Sn 2+ and Sn 4+ The conventional CBD process for preparing SnO x It is usually carried out in a closed container filled with air. As the reaction proceeds, the oxygen in the container will be gradually consumed as the hydrolysis time increases, resulting in a decrease in oxygen partial pressure. Changes in oxygen partial pressure will affect Sn 2+ and Sn 4+ The ratio of SnO x The band structure of the deposited SnO x However, in order to prepare SnO with a suitable band structure x The SnO layer requires a long reaction time, which makes x The increase in layer thickness is not conducive to the preparation of efficient perovskite solar cells.
[0004] Therefore, how to regulate the hydrolysis process of CBD to achieve SnO x The regulation of layer thickness and band structure is crucial for the preparation of efficient and stable photovoltaic devices. Summary of the invention
[0005] The present invention aims to solve the problem of preparing SnO by the existing CBD process. xIn order to solve the technical problem that the energy band structure of thin films is difficult to precisely control, a method for preparing tin oxide thin films by chemical bath deposition under inert atmosphere protection is provided. The method can be applied to industrial CBD deposition under inert atmosphere protection and applied to the electron transport layer of perovskite solar cells to prepare devices with excellent photovoltaic performance.
[0006] The inventive concept of the present invention is to use inert atmosphere protection to avoid SnO x The deposition process is affected by the oxygen partial pressure; at the same time, SnCl4 is introduced into the SnCl2 solution to precisely control the Sn in the precursor solution. 2+ and Sn 4+ The ratio of CBD can be adjusted to regulate the hydrolysis process of CBD, thereby achieving simultaneous x The thickness and band structure of the layer can be regulated to prepare Sn with appropriate thickness more quickly. 2+ and Sn 4+ Adjustable ratio SnO x Thin film, thus achieving SnO x Precise regulation of the band structure. x The film is used as an electron transport layer in perovskite solar cells, which can achieve a photoelectric conversion efficiency of more than 26%, and has excellent industrial application value and prospects.
[0007] In order to solve the above technical problems, the first aspect of the present invention provides a method for preparing a tin oxide thin film, comprising the following steps:
[0008] (1) adding a precursor solution into a reaction container having a conductive substrate, filling the container with an inert gas and sealing the container; the precursor solution contains SnCl2 and SnCl4;
[0009] (2) heating the sealed reaction container, taking out the conductive substrate after the thin film is deposited on the surface of the conductive substrate, and sequentially performing cleaning, ultrasonication, and annealing treatment to obtain the tin oxide thin film.
[0010] As a further improvement of the above scheme, the steps for preparing the precursor solution are:
[0011] Mix water, hydrochloric acid, stannous chloride dihydrate, urea and thioglycolic acid, and continue stirring in an ice bath during the mixing process; then mix the resulting solution with water to obtain a SnCl2 solution;
[0012] After mixing tin tetrachloride pentahydrate and water, a SnCl4 solution is obtained;
[0013] The SnCl2 solution and the SnCl4 solution are mixed to obtain the precursor solution.
[0014] Preferably, the concentration of the SnCl2 solution is 0.003-0.007 mol / L.
[0015] Preferably, the concentration of the SnCl4 solution is 0.45-0.60 mol / L.
[0016] Preferably, the volume ratio of the SnCl2 solution to the SnCl4 solution is 150:(0.1-0.3).
[0017] Preferably, the water is deionized water or distilled water, and tap water should not be used directly to avoid contamination of the product by mineral impurities and the like, which may interfere with the regulation of the energy band structure.
[0018] Preferably, the steps for preparing the precursor solution are:
[0019] Deionized water, hydrochloric acid, stannous chloride dihydrate, urea and thioglycolic acid are mixed; the mixture is stirred in an ice bath during the preparation process and the temperature is controlled below 5°C; the volume ratio of the deionized water, hydrochloric acid and thioglycolic acid is (300-500):(3-6):(0.07-0.2), the mass ratio of the stannous chloride dihydrate and urea is (1-1.2):(5-6), and the mass volume ratio of the stannous chloride dihydrate to deionized water is (0.2-0.4) g:100 mL; the obtained solution is mixed with deionized water in a volume ratio of (0.5-1.2):(1-5) to prepare a SnCl2 solution with a molar concentration of 0.003-0.007 mol / L;
[0020] Add tin tetrachloride pentahydrate to deionized water, mix well and perform ultrasonic treatment to prepare a SnCl4 solution with a molar concentration of 0.45-0.60 mol / L, and refrigerate for later use;
[0021] Take SnCl2 solution and SnCl4 solution in a volume ratio of 150:(0.1-0.3) and mix them evenly to obtain the precursor solution.
[0022] Preferably, the inert gas is nitrogen, and the purity of the nitrogen is above 99%, and it is necessary to ensure that the gas completely fills the reaction container.
[0023] Preferably, in step (2), the heating temperature is 70-90°C.
[0024] Preferably, in step (2), the heating time is 1.5-2 hours.
[0025] Preferably, in step (2), the annealing temperature is 160-190°C.
[0026] Preferably, in step (2), the annealing treatment time is 0.5-1.5 hours.
[0027] Preferably, in step (2), after the substrate on which the thin film is deposited is taken out, it is rinsed with deionized water or distilled water and ultrasonicated multiple times to ensure that the washing liquid after ultrasonication is free of particles and has a neutral pH, thereby ensuring complete rinsing to prevent impurities from affecting the performance of the thin film.
[0028] Preferably, in step (1), the conductive substrate is FTO conductive glass treated with ultraviolet ozone (UVO).
[0029] Preferably, the time after UVO treatment is 10-20 minutes.
[0030] The second aspect of the present invention provides a tin oxide film, which is prepared by the above preparation method, and has a thickness of about 20-22 nm. Tin oxide films with uniform thickness are conducive to the preparation of efficient perovskite solar cells.
[0031] A third aspect of the present invention provides a perovskite solar cell, wherein the perovskite solar cell comprises the above-mentioned tin oxide thin film.
[0032] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:
[0033] (1) The present invention adopts inert atmosphere protection to avoid SnO x The deposition process is affected by the oxygen partial pressure, and SnCl4 is introduced into the SnCl2 solution to precisely control the Sn 2+ and Sn 4+ By regulating the hydrolysis process of CBD, the SnO x The thickness and band structure of the layer can be regulated to prepare Sn with appropriate thickness more quickly. 2+ and Sn 4+ Adjustable ratio SnO x Thin film, thus achieving SnO x Precise control of the band structure.
[0034] (2) The present invention shortens the reaction process by protecting the inert atmosphere, and the obtained SnO x The film thickness is moderate, and the device performance will not be affected by the thickness factor. SnO with various energy band structures and moderate thickness can be prepared. x film.
[0035] (3) The present invention adopts a simple inert atmosphere protection and a chemical bath deposition technology suitable for industrial large-scale preparation, which can be applied to the preparation and optimization of industrial electron transport layers, and is conducive to the preparation of electron transport layer thin film materials with various energy band structures to match perovskite light absorption layer materials with different components. At the same time, the preparation method of the present invention has the advantages of high repeatability, simple operation, low cost, etc. The prepared SnO x The film exhibits an adjustable energy band structure. When applied to perovskite solar cells, the photoelectric conversion efficiency exceeds 26%, which has excellent industrial application value and prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 Preparation of SnO for the CBD process of the present invention x Schematic diagram of the reaction vessel used for the film;
[0037] Figure 2 These are actual photos of the precursor solutions used in Comparative Examples 1-3 of the present invention at different deposition times;
[0038] Figure 3 These are actual photos of the precursor solutions used in Examples 1-3 of the present invention at different deposition times;
[0039] Figure 4 SnO prepared in Comparative Examples 1-3 and Examples 1-3 of the present invention x Schematic diagram of the energy band structure of the film;
[0040] Figure 5 SnO prepared in Comparative Examples 1-3 of the present invention x Scanning electron microscope (SEM) morphology of the film;
[0041] Figure 6 SnO prepared in Examples 1-3 of the present invention x SEM morphology of the film;
[0042] Figure 7 The photoelectric conversion efficiency (PCE) and open circuit voltage (V OC ), short-circuit current density (J SC ) and fill factor (FF). DETAILED DESCRIPTION
[0043] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.
[0044] The preparation of the precursor solution and the preparation process conditions used in the following examples and comparative examples are as follows:
[0045] 1. Prepare SnCl2 solution: add 400mL deionized water, 5mL hydrochloric acid, 1.05-1.15g stannous chloride dihydrate, 4.8-5.2g urea and 100μL thioglycolic acid to a 500mL Shu Niu bottle in sequence; stir continuously in an ice bath during the preparation process and control the temperature below 5°C; mix the solution with deionized water in a volume ratio of 1:1 to prepare a SnCl2 solution, marked as solution A.
[0046] 2. Prepare SnCl4 solution: Add 1.5-2.1 g of tin tetrachloride pentahydrate to 10 mL of deionized water, mix well and ultrasonicate to prepare SnCl4 solution, refrigerate for later use, and mark it as solution B.
[0047] 3. Prepare different proportions of Sn 2+ / Sn 4+ Mixed solution: Take 150 mL of solution A and 0-300 μL of solution B and mix them evenly as the precursor solution for chemical bath deposition.
[0048] 4. Prepare the perovskite precursor solution (FAPbI3 solution): 1.53mmol of lead iodide, 1.4mmol of formamidine hydroiodide, and 0.5mmol of methylamine hydrochloride powder are added to a mixed solution of 0.8mL of N,N-dimethylformamide (DMF) and 0.1mL of dimethyl sulfoxide (DMSO), and shaken for 1 hour until completely dissolved. The solution needs to be spin-coated immediately after preparation to avoid crystallization in the solution due to long-term storage.
[0049] 5. Spin coating process parameters of FAPbI3 perovskite precursor solution: The spin coating step is divided into two steps. The first step has a rotation speed of 1000 rpm and a time of 10 seconds; the second step has a rotation speed of 5000 rpm and a time of 30 seconds (the acceleration is 2000 rpm / s). The whole process lasts for 40 seconds. 120 μL of ethyl acetate is added 20 seconds after the start of spin coating. The obtained film is annealed on a hot plate at 100°C for 1 hour.
[0050] 6. The spin coating process of the i-butylammonium iodide / potassium bis(fluorosulfonyl)imide (iBAI / K-FSI) upper interface layer must be a dynamic spin coating process with a rotation speed of 5000 rpm.
[0051] 7. The spin coating process of FAPbI3, iBAI / K-FSI upper interface and Spiro-OMeTAD (perovskite transport material) layer must be carried out in an inert atmosphere environment (H2O <1ppm, O2 <1ppm) to prevent water and oxygen from affecting the quality of the film.
[0052] Example 1
[0053] A method for preparing a tin oxide thin film comprises the following steps:
[0054] (1) Wipe the surface of the FTO glass substrate etched by the femtosecond laser with a dust-free cloth dipped in detergent to remove surface stains until the surface of the substrate can be wetted by water, and then put the substrate into a container containing detergent, deionized water and ethanol for 30 minutes each to ensure that the surface of the glass substrate is clean and free of stains. Subsequently, blow dry the glass surface with an air gun, wrap it with a dust-free cloth for standby use, and place it in a UV ozone cleaning machine for 15 minutes before use to obtain UVO-treated FTO glass;
[0055] (2) Figure 1 As shown, a precursor solution 3 (150 mL of solution A and 100 μL of solution B) is added to a reaction container 1, and the FTO conductive glass 2 treated in step (1) is placed at the same time; the reaction container 1 is filled with N2 and sealed, and heated at 90°C for 1.5-2 hours. After the reaction is completed, the FTO substrate is cleaned with deionized water for 1-3 minutes, followed by ultrasonic treatment for 30-90 seconds; the cleaned substrate is blown dry with an air gun and annealed at 160°C for 1.5 hours to obtain a SnO x The FTO substrate of the thin film is labeled as T2-5% substrate.
[0056] A method for preparing a perovskite solar cell comprises the following steps:
[0057] 1) The prepared FAPbI3 perovskite precursor solution (1.53 mmol lead iodide, 1.4 mmol formamidine hydroiodide, 0.5 mmol methylamine hydrochloride, 0.8 mL DMF and 0.1 mL DMSO) was shaken for 1 hour for later use. The T2-5% substrate was cut into 1×1.5 cm 2The film was prepared by spin coating, and the whole spin coating process was carried out in a nitrogen glove box. The spin coating step was divided into two steps. The first step was at a speed of 1000 rpm for 10 seconds; the second step was at a speed of 5000 rpm for 30 seconds (the acceleration was 2000 rpm / s). The whole process lasted for 40 seconds. 120 μL of ethyl acetate was added at 20 seconds after the start of spin coating, and the obtained film was annealed on a hot plate at 100°C for 1 hour.
[0058] 2) Dissolve 2 mg of iBAI and 2.8 mg of K-FSI in 1 mL of isopropyl alcohol / tetrahydrofuran (IPA / THF) mixed solvent (volume ratio 95:5). After the substrate is cooled, 30 μL of iBAI / K-FSI solution is dynamically spin-coated on the FAPbI3 perovskite layer at 5000 rpm, and then annealed at 100 ° C for 10 min to obtain the iBAI / K-FSI upper interface layer.
[0059] 3) First, 0.091g of Spiro-OMeTAD powder, 1mL of chlorobenzene, 35.6μL of 4-tert-butylpyridine, 21μL of acetonitrile solution of lithium bis(trifluoromethanesulfonyl)imide (520g / L), and 11μL of acetonitrile solution of FK209 cobalt salt (300g / L) were mixed to prepare a Spiro-OMeTAD solution. The solution was spin-coated on the perovskite light-absorbing layer to obtain a Spiro-OMeTAD hole transport layer. The spin-coating parameters were a rotation speed of 3000rpm, an acceleration of 3000rpm, and the whole process lasted for 30 seconds to obtain a Spiro-OMeTAD hole transport layer.
[0060] 4) After the spin coating of Spiro-OMeTAD is completed, use a knife to scrape off the Spiro-OMeTAD, perovskite and SnO at both ends of the battery. x . Paste the gold vaporization mask plate, leaving the gold vaporization area. Deposit gold with a thickness of 80-100nm on the Spiro-OMeTAD hole transport layer by vacuum evaporation to form a gold counter electrode to produce a perovskite solar cell.
[0061] Example 2
[0062] Referring to the method for preparing the tin oxide thin film of Example 1, only step (2) is changed. The specific steps are as follows:
[0063] Add 150 mL of solution A and 200 μL of solution B to the reaction container, and put in the FTO glass treated in step (1). Fill the reaction container with N2 and seal it, heat it at 90°C for 1.5-2 hours, and after the reaction is completed, use deionized water to clean the FTO glass for 1-3 minutes, and then ultrasonicate it for 30-90 seconds. Blow dry the cleaned substrate with an air gun and anneal it at 170°C for 1 hour to obtain a SnO x The FTO substrate of the thin film is labeled as T2-10% substrate.
[0064] The preparation method of the perovskite solar cell of Example 2 is the same as that of Example 1.
[0065] Example 3
[0066] Referring to the method for preparing the tin oxide thin film of Example 1, only step (2) is changed. The specific steps are as follows:
[0067] Add 150 mL of solution A and 300 μL of solution B to the reaction container, and put in the FTO glass treated in step (1). Fill the reaction container with N2 and seal it, heat it at 90°C for 1.5-2 hours, and after the reaction is completed, use deionized water to clean the FTO glass for 1-3 minutes, and then ultrasonicate it for 30-90 seconds. Blow dry the cleaned substrate with an air gun and anneal it at 180°C for 1 hour to obtain a SnO x The FTO substrate of the thin film is labeled as T2-15% substrate.
[0068] The preparation method of the perovskite solar cell of Example 3 is the same as that of Example 1.
[0069] Comparative Example 1
[0070] Referring to the method for preparing the tin oxide thin film of Example 1, only step (2) is changed. The specific steps are as follows:
[0071] Add 150 mL of solution A to the reaction container and put in the FTO glass treated in step (1). Seal the reaction container and heat at 70°C for 1.5-2 hours. After the reaction is completed, use deionized water to clean the FTO glass for 1-3 minutes, and then ultrasonicate for 30-90 seconds. Blow dry the cleaned substrate with an air gun and anneal at 160°C for 1.5 hours to obtain a SnO x The FTO substrate of the thin film is marked as C2 substrate.
[0072] The preparation method of the perovskite solar cell of Comparative Example 1 is the same as that of Example 1.
[0073] Comparative Example 2
[0074] Referring to the method for preparing the tin oxide thin film of Example 1, only step (2) is changed. The specific steps are as follows:
[0075] Add 150 mL of solution A to the reaction container and put in the FTO glass treated in step (1). Seal the reaction container and heat at 80°C for 3-3.5 hours. After the reaction is completed, use deionized water to clean the FTO glass for 1-3 minutes, and then ultrasonicate for 30-90 seconds. Blow dry the cleaned substrate with an air gun and anneal at 170°C for 1 hour to obtain a SnO x The FTO substrate of the thin film is marked as C3 substrate.
[0076] The preparation method of the perovskite solar cell of Comparative Example 2 is the same as that of Example 1.
[0077] Comparative Example 3
[0078] Referring to the method for preparing the tin oxide thin film of Example 1, only step (2) is changed. The specific steps are as follows:
[0079] Add 150 mL of solution A to the reaction container and put in the FTO glass treated in step (1). Seal the reaction container and heat at 95°C for 5-5.5 hours. After the reaction is completed, wash the FTO glass with deionized water for 1-3 minutes and then ultrasonicate for 30-90 seconds. Blow dry the washed substrate with an air gun and anneal at 190°C for 0.5 hours to obtain a SnO x The FTO substrate of the thin film is marked as C5 substrate.
[0080] The preparation method of the perovskite solar cell of Comparative Example 3 is the same as that of Example 1.
[0081] Performance Testing
[0082] 1. Appearance of tin oxide precursor solution
[0083] Figure 2 The following are the actual photos of the precursor solution used in the process of preparing the tin oxide thin film in Comparative Examples 1-3 under laser irradiation at different deposition times. Figure 2 It can be seen that as the reaction time increases, the oxygen in the container participates in the reaction, and Sn 2+ Gradually transformed into Sn 4+ , causing the turbidity of the solution to gradually increase.
[0084] Figure 3 The following are photos of the precursor solution used in the process of preparing the tin oxide thin film in Examples 1-3 under laser irradiation at different deposition times. Figure 3 It can be seen that at the same reaction time, the solutions of T2-5% and T2-10% are significantly clearer than C2, while the solution of T2-15% is more turbid than C2, indicating that Sn 4+The doping concentration directly determines the solution turbidity and is no longer affected by the oxygen partial pressure.
[0085] 2. Band structure of tin oxide thin film
[0086] Figure 4 SnO prepared in Comparative Examples 1-3 and Examples 1-3 of the present invention x Schematic diagram of the energy band structure of the film, from Figure 4 It can be seen that the energy band structure of the tin oxide prepared in Comparative Examples 1-3 using the conventional process gradually shifts downward as the reaction time increases; while the energy band structure of the tin oxide prepared in Examples 1-3 using the nitrogen-protected CBD process gradually shifts upward as the SnCl4 doping amount increases. By comparing with the conduction band of perovskite, it can be determined that the T2-10% tin oxide film has a good energy band match with the perovskite film.
[0087] 3. Microstructure of tin oxide film
[0088] Figure 5 and Figure 6 The SEM surface and cross-sectional images of the tin oxide films prepared in Comparative Examples 1-3 and Examples 1-3 are shown in FIG. Figure 5 It can be seen that there are obvious particle protrusions in the tin oxide morphology of C2 and C3, while there are obvious cracks on the surface of the tin oxide of C5. x The thickness of the layer fluctuates greatly, and the thickness increases significantly with time. Figure 6 It can be seen that the morphology of SnO2 with a content of T2-5%, T2-10% and T2-15% is uniformly covered with fine particles. x The layer shows the characteristics of dense conformal growth, and its thickness is uniform, about 20-22nm. Figure 5 and Figure 6 The SEM morphology shows that the nitrogen-protected CBD process can effectively improve the surface morphology of the tin oxide layer.
[0089] 4. Photovoltaic performance of perovskite solar cells
[0090] The perovskite solar cells prepared in Examples 1-3 and Comparative Examples 1-3 were tested under the conditions of one sun (AM1.5G, 100 mW / cm 2 ), calibrated with standard silicon cells, with a test area of 0.1486cm 2 ,The results of reverse scanning are shown in Table 1.
[0091] Table 1:
[0092]
[0093] Figure 7 The photoelectric conversion efficiency (A), open circuit voltage (B), short circuit current density (C) and fill factor (D) of the perovskite solar cells prepared in Comparative Examples 1-3 and Examples 1-3 of the present invention are shown in the following figure. Figure 7 As can be seen from Table 1, the efficiency of the perovskite solar cell device obtained by preparing tin oxide in Comparative Examples 1-3 using the conventional process first increases and then decreases with the increase of deposition time. Among them, the highest efficiency is the device based on C3, with a maximum efficiency of 24.44%, and its corresponding open circuit voltage is 1.151V and short circuit current is 25.81mA / cm 2 , the filling factor is 0.823. The efficiency of the device prepared based on the nitrogen protection CBD process first increases and then decreases with the increase of SnCl4 doping amount. Among them, the highest average efficiency is the device based on T2-10%, with a maximum efficiency of 26.01%, and its corresponding open circuit voltage is 1.184V and short circuit current is 26.09mA / cm 2 , the filling factor is 0.842.
[0094] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.
Claims
1. A method for preparing a tin oxide thin film, characterized in that: The following steps are involved: (1) adding a precursor solution into a reaction container having a conductive substrate, filling the container with an inert gas and sealing the container; the precursor solution contains SnCl2 and SnCl4; (2) heating the sealed reaction container, taking out the conductive substrate after the thin film is deposited on the surface of the conductive substrate, and sequentially performing cleaning, ultrasonication, and annealing treatment to obtain the tin oxide thin film.
2. The method for preparing a tin oxide thin film according to claim 1, characterized in that: The steps for preparing the precursor solution are: Mix water, hydrochloric acid, stannous chloride dihydrate, urea and thioglycolic acid, and continue stirring in an ice bath during the mixing process; then mix the resulting solution with water to obtain a SnCl2 solution; After mixing tin tetrachloride pentahydrate and water, a SnCl4 solution is obtained; The SnCl2 solution and the SnCl4 solution are mixed to obtain the precursor solution.
3. The method for preparing a tin oxide thin film according to claim 2, characterized in that: The molar concentration of the SnCl2 solution is 0.003-0.007 mol / L; and / or the concentration of the SnCl4 solution is 0.45-0.60 mol / L; the volume ratio of the SnCl2 solution to the SnCl4 solution is 150:(0.1-0.3).
4. The method for preparing a tin oxide thin film according to claim 2, characterized in that: The water is deionized water or distilled water.
5. The method for preparing a tin oxide thin film according to claim 1, characterized in that: In step (2), the heating temperature is 70-90° C.; and / or the heating time is 1.5-2 hours.
6. The method for preparing a tin oxide thin film according to claim 1, characterized in that: In step (2), the annealing treatment temperature is 160-190° C.; and / or the annealing treatment time is 0.5-1.5 hours.
7. The method for preparing a tin oxide thin film according to claim 1, characterized in that: In step (1), the inert gas is nitrogen, and the purity of the nitrogen is above 99%.
8. The method for preparing a tin oxide thin film according to claim 1, characterized in that: In step (1), the conductive substrate is FTO conductive glass treated with ultraviolet ozone.
9. A tin oxide thin film, characterized in that: The tin oxide film is prepared by the preparation method according to any one of claims 1 to 8, and the thickness of the tin oxide film is 20-22 nm.
10. A perovskite solar cell, characterized in that: The perovskite solar cell comprises the tin oxide thin film according to claim 9.
